Physical, nutritional, psychological, social and educational impacts on young people with Chronic Kidney Disease in their treatment (Research, Society and Development, 2021)
According to the Brazilian Society of Nephrology (SBN) in 2013 Brazil had 50,961 patients undergoing hemodialysis treatment due to CKD. Such data reveal that 5.6% are patients aged 13 to 18 years, although the number is not so significant, there is a gradual development of new cases in children and adolescents, the result of this research serves as a warning for the society. This is an integrative literature review article, using articles from the years 2011 to 2021, excluding theses, dissertations, monographs and non-relevant texts. Chronic kidney disease is a pathology at a critical level, which dialysis treatment is very invasive, causing physical and nutritional limitations and emotional and psychological imbalance.